HR Disruption—Time Already to Reinvent Talent Management. Issue 3 (July 2019) - Claus, Lisbeth
Rapid changes in demographics, technology and globalization have considerable global implications for work and the worker. This new context is also disrupting talent management as known for the last two decades. Progressive companies in all sectors realize that their talent management practices are no longer meeting the needs of their workers. Instead, employers focus their attention on developing a meaningful employee experience to attract and nurture the talent they need. A new breed of talent management practitioners is developing an HR stack that includes other management frameworks such as design thinking, agile management, behavioral economics and analytics to augment their HR competencies. Organizations will be unable to reinvent their existing talent management practices in a sustainable way unless they broaden the talent management conversation.